Exact traveling wave solutions for resonance nonlinear Schrödinger equation with intermodal dispersions and the Kerr law nonlinearity. (12th August 2019) - M. Srivastava, Hari; Günerhan, Hatira; Ghanbari, Behzad
Abstract : The main aim of this article is to present some new exact solutions of the resonant nonlinear Schrödinger equation. These solutions are derived by using the generated exponential rational function method (GERFM). The kink‐type, bright, dark, and singular soliton solutions are reported, and several numerical simulations are also included. The calculations are carried out by Maple software. All of the solutions that are derived in this paper are believed to be new and have presumably not been reported in earlier publications.